2010
DOI: 10.1088/0256-307x/27/12/124502
|View full text |Cite
|
Sign up to set email alerts
|

Static Structure of Two-Dimensional Granular Chain

Abstract: Static Structure of Two-Dimensional Granular Chain * WEN Ping-Ping( ), LI Liang-Sheng( ), ZHENG Ning( ), SHI Qing-Fan( )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The similar behavior between jamming state of granular chains with glass state of polymers was thus illustrated [17]. Our experiments subsequently revealed that statistical scaling characteristics of two-dimensional granular chains are in good accord with the theoretical expectations of polymer models [18][19][20].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The similar behavior between jamming state of granular chains with glass state of polymers was thus illustrated [17]. Our experiments subsequently revealed that statistical scaling characteristics of two-dimensional granular chains are in good accord with the theoretical expectations of polymer models [18][19][20].…”
Section: Introductionsupporting
confidence: 79%
“…The previous contributions on the static packing of granular chains mainly put emphasis on the packing structures near the jamming transition [17,21], or on an analogy between their statistical properties and theoretical predictions in polymer science [17][18][19][20], aiming to provide a possible way to uncover the physics that is experimentally inaccessible for polymers. Although the packing column confined in a container can also act as a simple but valid experimental system to test many theoretical models for the repartition or the transmission of stresses in granular materials [22][23][24][25], the mechanical behavior of the packing of granular chains did not receive enough attention until Brown et al revealed that a stress response in granular chains was very distinct from common grains, namely individual grains [26].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the locking of the beads in the chain ensembles, which arises out of the reduced degrees of freedom for beads embedded in the chains, granular chain behaviour is also dictated by the topological entanglement or topological knotting of the chains, especially for the longer chain lengths. 35–39,43 This property is well-studied in polymer melts and textile fibres. 86–89 The looping, curving, and knotting of the chains restricts the movement of the chains and improves the rigidity of the ensemble.…”
Section: Resultsmentioning
confidence: 99%
“…Macroscopic flexible granular chains form an exciting class of granular materials and have a wide range of applications in engineering and manifestations in nature. 42 From a purely mechanistic perspective, flexible granular chains exhibit an array of intriguing properties such as shear stiffening, 35,41 jamming at very low densities, 37,39,43 higher rigidity at lower coordination numbers 36 and many other entanglement-induced emergent behaviours. 44…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation